11 - Electrospun Nanofibers for Biosensing Applications - Murthe, Satisvar Sundera (Elsevier, 2019)
In this chapter, the basics of electrospinning technology, spanning from its humble beginnings to its current multifaceted utilizations in the field of biosensing, is covered. The chapter begins with the introduction to the mechanisms of electrospinning and the fundamental requirements for electrospinning. Next, the various crucial parameters that play a vital role in determining the final outcome of the nanofibers produced are discussed, with focus on the diverse outcomes due to manipulation of the parameters. The parameters range from the effects of applied voltage, which can be readily manipulated utilizing the electrospinning setup, to the ambient parameters, such as humidity and temperature, that are much harder to control, unless in a controlled environment. The chapter also discusses the necessity and logic of utilizing electrospun nanofibers as biosensing materials. Further in the chapter, the authors specifically discuss the myriad applications of electrospun nanofibers as biosensing elements. In particular, the authors review the selectivity and sensitivity of the nanofibers that account for the accurate sensing of the various bio-targets, and the conductivity of the nanofibers, which permits the rapid detection of the targets. Last but not least, the chapter discusses the use of nanofibers as membranes and electrodes, as biosensors that are able to deliver results efficiently and accurately.